Epicardial adipose tissue density and volume are related to subclinical atherosclerosis, inflammation and major adverse cardiac events in asymptomatic subjects - Goeller, Markus; Achenbach, Stephan; Doris, Mhairi K.; Cadet, Sebastien; Commandeur, Frederic; Chen, Xi; Slomka, Piotr J.; Gransar, Heidi; Cao, J. Jane; Wong, Nathan D.; Albrecht, Moritz H.; Rozanski, Alan; et al. (Journal of Cardiovascular Computed Tomography, 2018)
BACKGROUND: We investigated whether epicardial adipose tissue (EAT) volume and density are related to early atherosclerosis, plaque inflammation and major adverse cardiac events (MACE, cardiac death and myocardial infarction) in asymptomatic subjects. METHODS: EAT volume and density were quantified from non-contrast cardiac CT in 456 asymptomatic individuals (age 60.3 ± 8.3; 68% with CCS>0) from the prospective EISNER trial. EAT volume and density were examined in relation to coronary calcium score (CCS), inflammatory biomarkers and MACE. RESULTS: EAT volume was higher and EAT density lower in subjects with coronary calcium compared to subjects without [89 vs 74 cm3, p < 0.001] [-76.9 vs -75.7 HU,p = 0.024]. EAT volume was lowest in individuals with no coronary calcium and was significant higher in subjects with early atherosclerosis (CCS 1-99) [74 vs 87 cm3,p = 0.016] and in subjects with more advanced atherosclerosis (CCS≥100) [89 cm3,p = 0.002]). EAT volume was independently related to serum levels of PAI-1, and MCP-1 and inversely related to adiponectin and HDL-cholesterol (p < 0.05). EAT density was inversely related to PAI-1 and LDL-cholesterol and positively associated to adiponectin, sICAM-1 and HDL-cholesterol (p < 0.05). EAT density was more significantly associated with MACE [(HR 0.8, 95%CI:0.7-0.98), p = 0.029] than EAT volume or CCS. CONCLUSION: EAT volume was higher and density lower in subjects with coronary calcium compared to subjects with CCS = 0, with similar EAT volume in CCS<100 and CCS≥100. Lower EAT density and increased EAT volume were associated with coronary calcification, serum levels of plaque inflammatory markers and MACE, suggesting that dysfunctional EAT may be linked to early plaque formation and inflammation.
EVALuna2:33591